THE ROLE OF THE AUDITOR IN VERIFYING OF ACCOUNTING CONSERVATISMUSING THE (BTM) MODEL AND ITS IMPACT ON THE GOING CONCERN OF THE COMPANY (APPLIED RESEARCH IN A SAMPLE OF JOINT STOCK COMPANIES LISTED ON THE IRAQ STOCK EXCHANGE) - Muhnnad Talib Razouki, Prof. Dr. Sabiha Barzan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The research aims to evaluate the extent of applying the accounting conservatism from the auditor’s point of view by applying to fifteen joint stock companies within three sectors (industry, financial investment, insurance) and listed on the Iraq Stock Exchange for the period from (2015-2019). The accounting conservatism was measured using the book value to market value (BTM) model, and it was found that there is a difference in the levels of accounting conservatism for the companies, the research sample and the presence of a weak impact on the going concern of the company. In addition to the need for the external auditor to adopt the measurement models adopted by this research in examining the level of accounting conservatism and financial failure of the companies under audit to reach evidences that support his opinion of the extent of the companies ability to continue.